Severe Acral Necrosis Complicating Thrombotic Microangiopathy in Two Toddlers - H. Nassih; Z. Lazrak; S. Younous (Case Reports in Pediatrics)
Acral ischemia/necrosis is one of the rarest but most dreadful complications of thrombotic microangiopathy in pediatric patients. It is more reported with thrombotic thrombocytopenic purpura than with hemolytic and uremic syndrome. Even with anticoagulant therapy, it is often irreversible, leading to amputation.